2011
DOI: 10.2310/jim.0b013e318206ffad
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 Promoter Polymorphisms in Normal Han Chinese Population: Frequencies and Effects on Inflammatory Markers

Abstract: IL-6 -174G/C and -597G/A are rare, but -634C/G is common in Han Chinese population, and the -634G allele is associated with circulating levels of IL-6 and C-reactive protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 55 publications
(84 reference statements)
8
18
0
Order By: Relevance
“…This finding is consistent with a previous report that the G-to-C polymorphism is extremely rare in Chinese [19]. In Japan only -174 GG genotype was detected, and the frequencies of -572 CC, GC and GG genotypes were 50%, 45% and 5%, respectively [20].…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with a previous report that the G-to-C polymorphism is extremely rare in Chinese [19]. In Japan only -174 GG genotype was detected, and the frequencies of -572 CC, GC and GG genotypes were 50%, 45% and 5%, respectively [20].…”
Section: Discussionsupporting
confidence: 82%
“…Our metaanalysis of 83 studies involving 44,735 cases and 60,747 controls did not show a significant association between the -174G>C polymorphism and cancer risk, including lung cancer (Liu et al 2012). Of note, the -174C allele is extremely rare in Asian, including Chinese (Gu et al 2008; Lim et al 2002; Zhai et al 2001; Pan et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Given the facts that haplotypes have more power to detect associations with risk of complex diseases than single polymorphism (Johnson et al 2001; Manolio et al 2008) and the G to C polymorphism at -174 of IL-6 is extremely rare in Asian, including Chinese (Gu et al 2008; Lim et al 2002; Zhai et al 2001; Pan et al 2011), we decided to examine the association of IL-6 haplotypes consisting of the two functional polymorphisms of IL-6 promoter (-6331T>C and -572C>G) with risk of lung cancer and to define the functional relevance of risk haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…7,39,40 The association of IL-6 polymorphism with higher serum CRP concentration maybe due to an increase in IL-6 gene transcription and the consequent effects of increasing levels of IL-6 on CRP gene expression. 9 Our previous report 9 along with the studies conducted in Japanese and Koreans 18,[41][42][43][44][45] indicated that IL-6 À634G allele was associated with higher circulating levels of IL-6 and CRP in eastern Asians. However, assessment of serum IL-6 and CRP levels concordant with IL-6 À634C/G polymorphism in patients with AF, especially in patients with AF with LA thrombus, is required in further study.…”
Section: Discussionmentioning
confidence: 95%